THE LEVEL OF ECONOMIC DEVELOPMENT AS A FACTOR SHAPING THE REGIONAL DISPARITIES - S. Totev (Trakia Journal of Sciences)
The results of some empirical studies within the EU determining the relationship between the achieved level of economic development and the specific economic structure on the one hand and the magnitude of intra-regional differences on the other are presented and analysed. Based on comparative analysis, the expected evolution of the regional disparities in Bulgaria are defined. The possibilities for pursuing a targeted policy for achieving regional economic convergence have been assessed.